Noncentrosymmetric Sulfide Oxide MZnSO (M = Ca or Sr) with Strongly Polar Structure as Novel Nonlinear Crystals - Reshak, Ali H.; Abbass, Nada M.; Bila, Jiri; Johan, Mohd Rafie; Kityk, Ivan (American Chemical Society, 2019)
We performed a comprehensive ab inito calculation to investigate the influence of substitution of Ca2+ (180 pm) by larger Sr2+ (200 pm) in MZnSO (M = Ca or Sr) on the structural properties and, hence, on the linear and nonlinear optical properties. The substitution of Ca2+ by Sr2+ in MZnSO causes a band gap reduction resulting in an influence on the photophysical properties and enhances the optic activity toward the visible region. The observation of linear optical properties reveals a band gap reduction on moving from Ca to Sr, and the whole spectral structure shifts toward lower energies. The substitution of Ca2+ by Sr2+ introduces an obvious enhancement in the anisotropy between the extraordinary and ordinary tensor components, as confirmed by the uniaxial anisotropy and birefringence favoring an important role in second harmonic generation (SHG) and optical parameter oscillator due to better fulfilling of phase-matching conditions. The calculations show that SrZnSO exhibits larger SHG and microscopic first hyperpolarizability (βijk) than CaZnSO. © 2019 American Chemical Society.